Error Rate Analysis of Quantum-Annealing-Aided Multi-User Detection in Power-Domain Nonorthogonal Multiple Access - Kouki Yonaga; Kenichi Takizawa; Masaru Inaba (IEEE Access)
We present the error rate performance of quantum-annealing-aided multiuser detection (QA-aided MUD), a signal detection approach that combines quantum annealing (QA) with conventional iterative multiuser detection (MUD). This method utilizes QA to compute log-likelihood ratios (LLR), improving signal detection and enhancing connectivity in power-domain nonorthogonal multiple access (PD-NOMA) systems. However, owing to the limited computational resources of the QA hardware, a detailed error-rate analysis was not performed. In this study, we extend QA-aided MUD to digital annealing techniques and evaluate the error rate performance of uplink PD-NOMA systems. Block error rate (BLER) analysis demonstrates that QA-aided MUD outperforms the conventional successive interference cancellation (SIC) method when difference of received signal strength corresponding to devices at base station is small. Moreover, we revealed that tuning the annealing parameters is crucial to obtain such better BLER performance. Additionally, we conducted evaluation on a bit error rate (BER) with a few instances to compare the performance of the QA hardware and digital annealing techniques. The results indicate that signal detection can be achieved using all the annealing techniques. Finally, we present the latest challenges, including an over-the-air (OTA) experiment using QA-aided MUD.